The Influence of Halal Awareness, Religiusity, Brand Image , and Price on Decisions to Purchase Halal Cosmetic Products With Preference as an Intervening Variable - Ilmi Farajun Rikza; Misbahul Munir; Abdul Wadud Nafis (Syntax Corporation Indonesia, 2023)
Understanding the concept of halal tayyiban is a predictor of consumer attitudes towards halal cosmetics so that this attitude can influence the intention to purchase halal cosmetics. In addition, it is important for producers to include halal certification/logos because both Muslim and non-Muslim consumers perceive halal-certified products as tastier, more hygienic and safer. So this shows that the more confident consumers are about the halalness of the product, the greater the consumer's liking (preference) for the product. The research stages in this journal began by distributing questionnaires directly to halal cosmetics consumers at Roxy Square Jember. The number of indicators in this research was 24 so that a sample of 120 respondents was obtained. The sampling method used in this research is non-probability sampling. Sampling used an incidental sampling approach. Data obtained from the results of distributing questionnaires will be processed and presented in quantitative form. The steps taken to convert questionnaire data into quantitative data are by giving a value to each item answered by the respondent.